1990
DOI: 10.1128/iai.58.9.3101-3108.1990
|View full text |Cite
|
Sign up to set email alerts
|

Protection of sheep against Chlamydia psittaci infection with a subcellular vaccine containing the major outer membrane protein

Abstract: An outer membrane (OM) preparation from elementary bodies (EBs) of Chlamydia psittaci (ovine abortion strain) was used to vaccinate pregnant ewes in a single subcutaneous dose and was found to achieve protection after subcutaneous challenge with infectious organisms. Inactivated purified EBs used as a single-dose vaccine also gave protection. The ratio of live to dead lambs was significantly higher in the vaccinated groups (16:1 and 15:1, respectively) than in the placebo group (8:9). Polyacrylamide gel electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 39 publications
(39 reference statements)
1
41
0
Order By: Relevance
“…Attempts to produce a vaccine against genital C. trachomatis infections began some decades ago. Efforts to vaccinate monkeys, mice, sheep, and guinea-pigs with C. trachomatis MOMP, which has been considered to be the best candidate for an acellular vaccine, have resulted in limited success (Taylor et al, 1988;Tan et al, 1990;Tuffrey et al, 1992;Batteiger et al, 1993;Su et al, 1995;Pal et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Attempts to produce a vaccine against genital C. trachomatis infections began some decades ago. Efforts to vaccinate monkeys, mice, sheep, and guinea-pigs with C. trachomatis MOMP, which has been considered to be the best candidate for an acellular vaccine, have resulted in limited success (Taylor et al, 1988;Tan et al, 1990;Tuffrey et al, 1992;Batteiger et al, 1993;Su et al, 1995;Pal et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, research has focused on the MOMP which is the predominant constituent of chlamydial outer membranes, comprising approximately 60% of the protein mass. The MOMP remains the only chlamydial protein shown unequivocally to be surface exposed, and antibodies specific to the protein have been shown to be protective (2,28,37). For these reasons, MOMP remains the primary candidate for a chlamydial vaccine.…”
Section: Discussionmentioning
confidence: 99%
“…Protein sequence comparisons of MOMPs both within (33) and between (18) species, combined with epitope mapping studies (8,43), have shown that the epitopes responsible for neutralization lie within four variable segments. Vaccine preparations based on chlamydial outer membrane complexes, which are highly enriched for the MOMP in its native form, have been shown to be protective against chlamydial disease in sheep (37), guinea pigs (2), and mice (10,28). However, experimental vaccines based on denatured or nonnative recombinant MOMP preparations have yielded, at best, only partial protection (28).…”
mentioning
confidence: 99%
“…The POMPs have been extensively analysed by 2-D electrophoretic analysis [11] and have been suggested to be important serodiagnostic antigen candidates [9,12]. They may also play a role in protective immunity since they are present in chlamydial outer membrane complexes [9,13,14] which have been shown to be protective [15]. However, such a role is not supported by the recent results of Buend| èa et al [6] who failed to demonstrate localisation to the EB surface.…”
Section: Introductionmentioning
confidence: 99%